Sistem Monitoring Pemakaian Energi Listrik Pada Kamar Kost Menggunakan Aplikasi Blynk Berbasis Internet of Things - Lulu Sabillah; Rahmat Hidayat (Jurnal Komputer dan Elektro Sains, 2023)
Currently, the electrical energy monitoring system can only be monitored by PLN. Electricity users can usually only see the amount of usage each month without knowing electricity usage at any time. Excessive use of electricity will cause payments to increase. Therefore, this research was conducted to monitor the electrical power used in boarding houses via an internet connection using the blynk application. This study aims to determine the amount of electrical energy consumption every day. This lot-based monitoring tool uses the PZEM-004T sensor to read the amount of electrical energy consumption such as voltage, current, power and energy. As for the media interface that displays the amount of electrical energy consumption using the LCD and the Blynk application.